유동인구 데이터를 활용한 한강공원의 이용 패턴과 특성 연구 - 홍성인; Hong Sung-in; 임저스틴희준; Lim Justin Heejoon; 최영준; Choi Youngjoon; 이제승; Lee Jae Seung (한국조경학회지, 2025)
본 연구는 서울시 한강공원 11개소를 대상으로 2023년 KT 유동인구 데이터를 활용하여, 시간대 및 연령대별 이용자 특성과 공원 내 공간 요소 간의 관계를 시공간적으로 분석하였다. 이를 위해 50m 격자 단위의 유동인구 데이터를 기반으로 평균 이용시각과 평균 연령을 가중평균 방식으로 산출하고, QGIS 기반 공간분석을 통해 이들의 분포특성을 도출하였다. 분석 결과, 한강공원은 시간대별로는 출퇴근 시간대를 중심으로 이용이 집중되는 경향이 나타났고, 연령대별로는 30-40대 이용자의 비중이 가장 높았다. 공간분석에서는 체육시설과 생태공간 인근에서 이른 평균 이용시각과 높은 평균 연령이, 대중교통 접근성이 우수하거나 야간 콘텐츠가 집중된 공간에서는 늦은 평균 이용시각과 낮은 평균 연령이 나타나는 등, 공간 요소별로 뚜렷한 이용 특성 차이가 확인되었다. 이는 공원의 이용패턴이 물리적 환경, 접근성, 시설 구성 등의 요인에 따라 다르게 나타난다는 점을 시사하며, 이는 고밀도 도시환경에서 공원의 쾌적성과 기능 향상을 도모하기 위한 전략적 접근의 일환으로, 시공간적 이용 특성을 반영한 공간 관리 및 운영 방안의 필요성을 시사한다 다만, 본 연구는 시간 단위 집계의 한계와 동적 이동 수단의 데이터 미포함 등 기술적 제약이 존재하며, 향후 보다 정밀한 분석을 위해 다양한 데이터의 보완이 요구된다. This study analyzed the spatiotemporal relationship between user characteristics by time of day and age group, and spatial elements within parks, using 2023 KT mobile population data for 11 locations along the Han River Parks in Seoul. To this end, average visit time and average age were calculated using weighted means based on 50m grid population data, and their spatial distributions were analyzed through QGIS-based spatial analysis. The analysis revealed that park usage tended to concentrate during commuting hours, and that users in their 30s and 40s accounted for the largest proportion. Spatial analysis showed distinct usage patterns depending on park features; areas near sports and ecological facilities were associated with earlier average visit times and higher average ages, while areas with strong public transit access or night-time cultural content tended to have later visit times and lower average ages. These findings suggest that park usage patterns vary depending on physical conditions, accessibility, and spatial programming. As part of a strategic approach to enhance the functionality and comfort of parks in high-density urban environments, the results underscore the need for park management and operation strategies that reflect spatiotemporal usage characteristics. However, this study is subject to technical limitations, such as the temporal resolution of the data and the exclusion of dynamic transportation modes, and future research will require the supplementation of diverse data sources for more refined analysis.